Electronic structure of multi-walled carbon fullerenes. (29th December 2016) - Doore, Keith; Cook, Matthew; Clausen, Eric; Lukashev, Pavel V; Kidd, Tim E; Stollenwerk, Andrew J
Abstract: Despite an enormous amount of research on carbon based nanostructures, relatively little is known about the electronic structure of multi-walled carbon fullerenes, also known as carbon onions. In part, this is due to the very high computational expense involved in estimating electronic structure of large molecules. At the same time, experimentally, the exact crystal structure of the carbon onion is usually unknown, and therefore one relies on qualitative arguments only. In this work we present the results of a computational study on a series of multi-walled fullerenes and compare their electronic structures to experimental data. Experimentally, the carbon onions were fabricated using ultrasonic agitation of isopropanol alcohol and deposited onto the surface of highly ordered pyrolytic graphite using a drop cast method. Scanning tunneling microscopy images indicate that the carbon onions produced using this technique are ellipsoidal with dimensions on the order of 10 nm. The majority of differential tunneling spectra acquired on individual carbon onions are similar to that of graphite with the addition of molecular-like peaks, indicating that these particles span the transition between molecules and bulk crystals. A smaller, yet sizable number exhibited a semiconducting gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) levels. These results are compared with the electronic structure of different carbon onion configurations calculated using first-principles. Similar to the experimental results, the majority of these configurations are metallic with a minority behaving as semiconductors. Analysis of the configurations investigated here reveals that each carbon onion exhibiting an energy band gap consisted only of non-metallic fullerene layers, indicating that the interlayer interaction is not significant enough to affect the total density of states in these structures.